International exchange rate systems: Where do we stand? - Horst Siebert (Kiel Institute for the World Economy (IfW), 2006)
This paper analyzes institutional arrangements for exchange rate systems and reviews what we know. It looks at the foreign exchange market, different balance of payment situations in which countries find themselves and the necessary exchange rate adjustments. It studies the options that are available to countries in choosing their exchange rate system (type of nominal anchor, nominal anchor versus real target and the degree of sovereignty to be given up) and reviews the historical experience for multilateral options. The actual system is a fragile low-inflation central bank dominated arrangement. Options for the future rest on quite a few idealistic ideas. In addition to choosing the exchange rate system, adopting the right exchange rate is also addressed.
Keywords: E42; F31; F32; E; F33; E5; E58; E61; 330; Balance of payments situations; External and internal equilibrium; Choosing the exchange rate system; Exchange rate systems; Internationales Währungssystem; Wechselkurssystem; Monetäre Außenwirtschaftstheorie; Theorie; Welt